1991
DOI: 10.1128/aac.35.9.1760
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactamase of Mycobacterium fortuitum: kinetics of production and relationship with resistance to beta-lactam antibiotics

Abstract: The kinetics of both intracellular and extracellular beta-lactamase production and the relationship between extracellular enzyme and in vitro susceptibility of Mycobacterium fortuitum to beta-lactam antibiotics have been studied. To this end we used a panel of stable nitrosoguanidine-induced mutants of M. fortuitum derived from the parental strain ATCC 19542 and differing in beta-lactamase production from 0.0001 to 278 U/liter in Mueller-Hinton broth. For overproducers of beta-lactamase (mutants A188, B180, C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…However, it is less clear whether they play a significant role in either intrinsic resistance or acquired resistance to ␤-lactams in NTM. Several studies of the ␤-lactamases of M. fortuitum found that the level of these enzymes did correlate with susceptibility to some ␤-lactams, such as amoxicillin, ampicillin, and benzylpenicillin (107,260,303). Similar results were found with M. smegmatis (113).…”
Section: Inhibition Of Mycobacterial Cell Wall Synthesissupporting
confidence: 76%
See 3 more Smart Citations
“…However, it is less clear whether they play a significant role in either intrinsic resistance or acquired resistance to ␤-lactams in NTM. Several studies of the ␤-lactamases of M. fortuitum found that the level of these enzymes did correlate with susceptibility to some ␤-lactams, such as amoxicillin, ampicillin, and benzylpenicillin (107,260,303). Similar results were found with M. smegmatis (113).…”
Section: Inhibition Of Mycobacterial Cell Wall Synthesissupporting
confidence: 76%
“…Porin loss has a significant fitness cost (362), which may outweigh the resistance benefit to the organism. Despite this, there is indirect evidence that the permeability barrier of the cell wall may play a critical role in the intrinsic resistance of mycobacteria to ␤-lactams (107,177,252,303).…”
Section: Inhibition Of Mycobacterial Cell Wall Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…1-Lactamase activity (released and cell bound) was determined spectrophotometrically with cephaloridine as the substrate (5). Susceptibility tests were conducted by using a twofold agar dilution method (5).…”
mentioning
confidence: 99%